Example 1 |
T(x, y) = (x/2, y/2) has fixed point (0, 0). |
|
(x, y) = T(x, y) = (x/2, y/2). So
x = x/2 and y = y/2, hence x = 0 and y = 0. |
Example 2 |
T(x, y) = (x/2, y/2) + (1/2, 0) has fixed point (1, 0). |
|
(x, y) = T(x, y) = (x/2, y/2) + (1/2, 0). So
x = x/2 + 1/2 and y = y/2, hence x = 1 and y = 0. |
Example 3 |
T(x, y) = (a⋅x, b⋅y) + (c, d) has fixed point (c/(1-a), d/(1-b)). |
|
(x, y) = T(x, y) = (a⋅x, b⋅y) + (c, d). So
x = a⋅x + c and y = b⋅y + d, hence x = c/(1-a) and
y = d/(1-b). We have assumed neither a nor b is 1. What happens if either
of these is true? |
|